Códigos de verificação de erros de paridade de baixa densidade (LDPC) - Mattos, Willian Daniel de (2012)
This monograph presents an ensemble of error control codes known as LDPC (Low Density Parity Check Codes). These codes were developed in the 70’s decade and have a great performance in a channel with a big amount of noise. Unlike other classes of codes, they are equipped with a very fast encoding and decoding algorithms, which makes them perfect for practical applications in telecommunication systems. The name came from the behavior of the parity check matrix, which has a low density of non-null elements. In order to allow the discussion of theses codes, some elements about digital communications systems e linear block codes are presented in the initial chapters. The LDPC codes will be defined in terms of the matrix representation and via bipartite graphs which are a graphical representation of the parity check matrix which make easier the comprehension of the iterative decoding process. Furthermore, the coding and decoding algorithms using different methods will be discussed, which the approach the capacity of the channel defined by Shannon is the main goal.